(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
This article discusses the problem of using tires for use in mountain conditions for mining and transporting rocks. In mountain conditions, crushed stone debris, characterized by high abrasive ability, distributed on a quarry road, is characterized by the fact that it is scattered on the hard base of the road surface, which leads to an increase in the intensity of abrasive wear of the tread pattern and, as a result, a reduction in tire service life. A number of measures to prevent tire wear are shown.